2022
DOI: 10.3390/en15145118
|View full text |Cite
|
Sign up to set email alerts
|

An Industrial Approach for the Optimization of a New Performing Coated Adsorber for Adsorption Heat Pumps

Abstract: In the present work, the optimization of a new coating formulation was investigated, taking attention to an industrially focused research approach used for the engineering design of the adsorber. The adsorbent was a composite zeolite or silica-gel based coating applied by using new flexible polymer matrices. The FC-80 formulation represents a good compromise between mechanical stability and absorption capacity. Using the developed coating process, a new compact HEX design was developed to reach the AHP target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…For the fabrication of binder-based adsorbent coating, the adsorbent powder is mixed with a binder and a solvent to obtain a slurry, which can be further deposited on the HEx surface by several methods [34]. The binder-based coating is a mature technique widely applied to obtain films of various adsorbents, including zeolite SAPO-34 [7], MOFs-aluminum fumarate [35], MIL-101(Cr), and HKUST-1 [36], MIL-160 [37], MIL-100(Fe) [38], composite sorbents LiCl/(Wakkanai siliceous shale) [39], etc. Various adhesive compounds of organic (PVA [35,40], polyvinylpyrrolidone [40,41], hydroxyethyl cellulose [35], silicones [36,42], silanes [20,43], gelatine [40], etc.)…”
Section: Binder-based Adsorbent Coatingsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the fabrication of binder-based adsorbent coating, the adsorbent powder is mixed with a binder and a solvent to obtain a slurry, which can be further deposited on the HEx surface by several methods [34]. The binder-based coating is a mature technique widely applied to obtain films of various adsorbents, including zeolite SAPO-34 [7], MOFs-aluminum fumarate [35], MIL-101(Cr), and HKUST-1 [36], MIL-160 [37], MIL-100(Fe) [38], composite sorbents LiCl/(Wakkanai siliceous shale) [39], etc. Various adhesive compounds of organic (PVA [35,40], polyvinylpyrrolidone [40,41], hydroxyethyl cellulose [35], silicones [36,42], silanes [20,43], gelatine [40], etc.)…”
Section: Binder-based Adsorbent Coatingsmentioning
confidence: 99%
“…The comparison of AHT with conventional compression technologies revealed that the main drawback of ACs and AHPs is their large size, which is related to low specific power (SP), and high equipment cost [5]. The high cost of about 1000 Euro/kW is compensated by lower operating costs and saves 60-80% of electricity [7]. The first adsorptive chillers of 50-1000 kW power entered the market as early as 1986 from two Japanese companies, Nishiyodo Kuchouki [8] and Mycom [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SP of AHTS systems is mainly affected by the dynamics of the adsorption and desorption stages of the working cycle, governed by coupled heat and mass transfer in the adsorber-heat exchanger (Ad-HEx) unit. In this vein, the optimization of the Ad-HEx 2 of 16 configuration is becoming a hot topic of research related to AHTS technology [4][5][6]. Nowadays, two basic Ad-HEx configurations are widely used, namely, the loose adsorbent grains loaded between the HEx fins and the thin adsorbent coating on the HEx surface [7,8].…”
Section: Introductionmentioning
confidence: 99%